Clinical and future applications of high intensity focused ultrasound in cancer - Al-Bataineh, Osama; Jenne, Jürgen; Huber, Peter E. (Cancer treatment reviews, 2012)
High intensity focused ultrasound (HIFU) or focused ultrasound (FUS) is a promising modality to treat tumors in a complete, non invasive fashion where online image guidance and therapy control can be achieved by magnetic resonance imaging (MRI) or diagnostic ultrasound (US). In the last 10 years, the feasibility and the safety of HIFU have been tested in a growing number of clinical studies on several benign and malignant tumors of the prostate, breast, uterine, liver, kidney, pancreas, bone, and brain. For certain indications this new treatment principle is on its verge to become a serious alternative or adjunct to the standard treatment options of surgery, radiotherapy, gene therapy and chemotherapy in oncology. In addition to the now clinically available thermal ablation, in the future, focused ultrasound at much lower intensities may have the potential to become a major instrument to mediate drug and gene delivery for localized cancer treatment. We introduce the technology of MRI guided and ultrasound guided HIFU and present a critical overview of the clinical applications and results along with a discussion of future HIFU developments.